1981
DOI: 10.1071/ar9810947
|View full text |Cite
|
Sign up to set email alerts
|

The relative growth and development of the carcass tissues of Merino and crossbred rams and wethers

Abstract: One hundred and twenty lambs were used to study the effects of breed (Merino or Dorset Horn x (Border Leicester x Merino)), sex (entire or castrate male) and liveweight (birth to 50 kg) on carcass conformation and composition. Merinos were lighter at birth and grew more slowly than crossbreds in both the pre- and post-weaning phases (P < 0.01). Rams grew significantly faster than wethers only after weaning (P < 0.01). Merinos exceeded crossbreds in height at withers and chest depth (P < 0.01), but the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
3
7

Year Published

1995
1995
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 0 publications
2
4
3
7
Order By: Relevance
“…Based on these reports, it is evident that that nutrient demands, absorption and partitioning in ewes is different from those of wethers and results in the utilization of Spirulina for increasing liveweight and body conformation. Previous studies demonstrated that genetic variation between lambs influences nutrient partitioning and absorption despite the feeding of the same or identical rations Lewis et al, 2006;Oddy and Sainz, 2002;Cake et al, 2007;Wynn and Thwaites, 1981). …”
Section: Discussionmentioning
confidence: 99%
“…Based on these reports, it is evident that that nutrient demands, absorption and partitioning in ewes is different from those of wethers and results in the utilization of Spirulina for increasing liveweight and body conformation. Previous studies demonstrated that genetic variation between lambs influences nutrient partitioning and absorption despite the feeding of the same or identical rations Lewis et al, 2006;Oddy and Sainz, 2002;Cake et al, 2007;Wynn and Thwaites, 1981). …”
Section: Discussionmentioning
confidence: 99%
“…According to Salako (2006a), body measurement in addition to weight measurements describes more completely an individual or population than do the conventional methods of weighing and grading. Various studies showed that body dimensions could be used to study the interaction between heredity and environment (Dunlop 1963), and in assessing growth rate, feed utilizations and carcass characteristics in farm animals (Wynn and Thwaites 1981) and live body weight can be predicted from body measurements (Aziz and Sharaby 1993;Mohammed and Amin 1997;Varade and Ali 1999;Atta and El Khidir 2004). Besides, linear size measurements have been suggested as more objective measures of body conformation of animals (Janssens and Vandepitte 2004).…”
Section: Introductionmentioning
confidence: 99%
“…WYNN & THWAITES (1981), trabalhando com cordeiros da raça Merina puros e cruzada (Border Leicester x Merina), observaram que os animais cruzados possuem maior quantidade de osso do que os animais puros quando comparados aos pesos de abate de 10; 40 e 50kg de peso vivo.…”
Section: Introductionunclassified